2008
DOI: 10.1021/nn700185t
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Single-Walled Carbon Nanohorns

Abstract: We extensively investigated in vitro and in vivo the toxicities of as-grown single-walled carbon nanohorns (SWNHs), a tubular nanocarbon containing no metal impurity. The SWNHs were found to be a nonirritant and a nondermal sensitizer through skin primary and conjunctival irritation tests and skin sensitization test. Negative mutagenic and clastogenic potentials suggest that SWNHs are not carcinogenic. The acute peroral toxicity of SWNHs was found to be quite low--the lethal dosage for rats was more than 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(181 citation statements)
references
References 81 publications
9
167
0
5
Order By: Relevance
“…23,90,93,94,99 In further animal tests, no abnormal body weight or clinical symptoms (including skin and eye irritation and lung tissue damage) were observed after the administration of SWNHs. 92,130 Negative mutagenic and clastogenic results suggest that SWNHs are not carcinogenic. Moreover, histopathological examinations revealed that SWNHs were retained in the liver, lungs and spleen of the tested animals.…”
Section: Toxicity Of Spherical Nanocarbon Materials-are Spherical Nanmentioning
confidence: 99%
“…23,90,93,94,99 In further animal tests, no abnormal body weight or clinical symptoms (including skin and eye irritation and lung tissue damage) were observed after the administration of SWNHs. 92,130 Negative mutagenic and clastogenic results suggest that SWNHs are not carcinogenic. Moreover, histopathological examinations revealed that SWNHs were retained in the liver, lungs and spleen of the tested animals.…”
Section: Toxicity Of Spherical Nanocarbon Materials-are Spherical Nanmentioning
confidence: 99%
“…Toxicological assessments of as-grown Single-walled Carbon Nanohorns (SWNHs) investigated by Miyawaki et al, under different exposure pathways. Results indicated that SWNHs have low toxicity because SWNHs not include metal catalyst [33].…”
Section: Non-metal Nanoparticlesmentioning
confidence: 99%
“…KNT'lerin fare ve sıçanlara uygulandığı birkaç çalışmada, akciğer, karaciğer ya da dalak gibi majör organlarda KNT birikiminden kaynaklanan olumsuz etkiler görülmüş-tür. Bu çalışmalarda KNT toksisitesinin uygulanma yoluyla da ilgili olabildiği de rapor edilmektedir (97)(98)(99)(100)(101)(102). KNT'lerin akciğer plevra dokusu ve mezotelyoma üzerine etkisi hakkındaki in vivo, in vitro ve de novo çalışmalar ise yok denecek kadar azdır (103).…”
Section: İlaç Taşinmasinda Nanotaşiyicilarin Dezavantajlariunclassified